Outcomes of kidney retransplantation in recipients with prior post‐transplant lymphoproliferative disorder. Issue 1 (January 2016) - Rouphael, Bassem; Lankireddy, Srilakshmi; Lazaryan, Aleksandr; Kukla, Aleksandra; Ibrahim, Hassan N.; Matas, Arthur J.; Issa, Naim
Abstract: Post‐transplant lymphoproliferative disease (PTLD) is an uncommon but serious complication of solid organ transplantation. Reduction in immunosuppression is the mainstay of PTLD treatment, but it may precipitate graft loss. Retransplantation remains controversial, as immunosuppression resumption may trigger PTLD relapse. Herein, we describe the experience of eight patients who underwent kidney retransplantation after successful PTLD treatment. Epstein–Barr virus (EBV) serology was not known before the first transplantation. PTLD was diagnosed 62.5 months (range 5–323 months) after transplantation and was confined to the renal allograft (n = 1), lymph nodes (n = 2), gastrointestinal tract (n = 4), or central nervous system (n = 1). Immunosuppression tapering (8/8), chemotherapy (6/8), oral cavity lymphoma excision (1/8), and allograft nephrectomy (1/8) led to hematological remission in all patients. Retransplantation was performed at a median of 55.5 months (range 29–95 months) after PTLD diagnosis. After a median follow‐up of 62.5 months (range 2–125 months) allograft survival was 87.5% (seven functioning grafts, one failed graft from chronic rejection), with no recurrence of PTLD. In all, five patients remain alive; the other three died from causes other than PTLD. In conclusion, kidney retransplantation appears to be safe in patients with prior PTLD and without major risk of hematological recurrence provided that PTLD has remitted.